2021
DOI: 10.3390/app11104706
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Real-Time 3D Path Planning for Autonomous Navigation of Unmanned Aerial Vehicle

Abstract: The need for civilian use of Unmanned Aerial Vehicles (UAVs) has drastically increased in recent years. Their potential applications for civilian use include door-to-door package delivery, law enforcement, first aid, and emergency services in urban areas, which put the UAVs into obstacle collision risk. Therefore, UAVs are required to be equipped with sensors so as to acquire Artificial Intelligence (AI) to avoid potential risks during mission execution. The AI comes with intensive training of an on-board mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…When moving in cluttered environments, collision-free reference trajectories are to be sought, to be followed by the vehicles. As path planing can be computationally demanding, a new light-weight planner is developed in [12] based on relative position of detected obstacles that can be used in real-time in a perception and control loop. Another approach is proposed in [13] that exploits obstacle geometry information to give priority to search in sub-spaces where a solution can be found quickly.…”
Section: Algorithms For Autonomymentioning
confidence: 99%
“…When moving in cluttered environments, collision-free reference trajectories are to be sought, to be followed by the vehicles. As path planing can be computationally demanding, a new light-weight planner is developed in [12] based on relative position of detected obstacles that can be used in real-time in a perception and control loop. Another approach is proposed in [13] that exploits obstacle geometry information to give priority to search in sub-spaces where a solution can be found quickly.…”
Section: Algorithms For Autonomymentioning
confidence: 99%
“…Tests of coverage paths it can be conducted with drones in a real or simulated environment. The most viable option for this stage of the work is simulation, as verified by other research [69][70][71][72]. Simulation has been recognized as an important research tool; initially, simulation was an academic research tool, but with the advancement of computers, simulation has reached new levels.…”
Section: Introductionmentioning
confidence: 97%
“…It is therefore suggested that there are two practical but important restrictions to blame for this gap between application demands and technology capabilities [4]. It is difficult to build and store a variety of target object models, especially when the objects have a variety of appearances, and real-time object detection requires ISSN: 2302-9285  high computing power even to detect single objects, much less when many target objects are involved, in addition to object recognition algorithms that are tailored to specific object and context types [5].…”
Section: Introductionmentioning
confidence: 99%